Analisis Kosakata Slang Bahasa Jepang (Wakamono Kotoba) dalam Anime pada Komunitas Medan Anime - Nasution, Laraiba; Siregar, Muhammad Yusuf (Program Studi Sastra Jepang, Universitas Jenderal Soedirman, 2023)
This study discusses the Analysis of Japanese Slang Vocabulary (Wakamono Kotoba) in Anime at the Medan Anime Club Community. This study aims to determine the interests of members of the Medan Anime Club in Japanese slang vocabulary (wakamono kotoba) and to find out what types of Japanese slang vocabulary (wakamono kotoba) are known by members of the Medan Anime Club. The theory used is a sociolinguistic theory, which is about language variations. The methodology used is the descriptive qualitative method. Respondents in this study were members of the Medan Anime Club as many as 45 people, both male and female. Each of these respondents will be distributed a questionnaire/questionnaire. The results of the questionnaire/questionnaire of the respondents will be the primary data source in this study. The data will be analyzed using an advanced technique, namely face-to-face or abbreviated as CTS. The members of the Medan Anime Club can learn Japanese by watching anime (animation) and also that 42 people are interested in speaking Japanese, in this case, Japanese slang vocabulary (wakamono kotoba) with a percentage of 93.3%. Furthermore, 32 people know about Japanese slang vocabulary (wakamono kotoba) with a percentage of 71.1%. The most widely known slang (wakamono kotoba) vocabulary by Medan Anime Club members is 7 people know baka and kimochi, 5 people know gomen, 4 people know nani, urusai, 3 people know Atashi, boku, souka, wakaranai, 2 people see the word aniki, kimi 2, itai, omae, yamete. Finally, 1 person knows dattebayo, konoyarou, sankyu, kisama, akuma, ikenai, shinjirarenai, aho, naze, yabai, yamerou, nandemonai, korose, nande, minna, teme, bakayarou, dekinai.